An Analysis of the Authorship and Co-authorship Networks of the Brazilian Human-Computer Interaction Conference - Franklin M. da C. Lima; Leonardo Cunha de Miranda; Gabriel Alves Mendes Vasiljevic; M. Cecília C. Baranauskas (Journal on Interactive Systems, 2024)
In Brazil, the Brazilian Symposium on Human Factors in Computing Systems (IHC) gathers the scientific community of researchers interested in the field of Human-Computer Interaction since 1998, being the main Brazilian event in this sub-area of Computing. Over twenty-one editions, the IHC received works from researchers from different regions of the country who, over the years, have been building their own co-authorship relationships with the other authors of the Symposium. In this context, this paper analysed the IHC from the perspective of those who helped to consolidate this important national scientific event, as well as in the expansion of the Human-Computer Interaction area in the Brazilian scenario, that is, its researchers-authors. In total, 1,443 authors were identified and analysed in the study presented in this work, which considered 873 publications of three IHC tracks: Full Papers, Short Papers, and Innovative Ideas and Emerging Results. Issues related to the publications and to the co-authorship relationships of these authors over the years and in the different article tracks of the IHC were considered. In order to describe their research trajectories within the IHC itself, the study presents, in different scales of time, how these authors evolved in relation to their contributions over time. In addition, this paper analyses how the authors contributed with each other and originated the complex collaboration network of the IHC. For this, co-authorship networks and groups of authors who published together were explored, aiming to clarify the collaborations between these authors, as well as how they evolved until the edition of 2022. In this sense, this work seeks, with each research question, to simplify the presentation of results through different visualizations, which were planned and created to describe information that are not clearly evident when observing the IHC publications in a “disconnected” manner. The results of this study are revealed, described and analysed under different perspectives, as well as discussed in details in this paper.